Synthetic biology approaches to negative emissions technologies: a technological and ethical appraisal - Logel, Dominic Y.; Wodak, Josh (Frontiers in Climate, 2025)
This article explores the impact that synthetic biology approaches may have on Negative Emissions Technologies (NETs). Synthetic biology has both altered and created biological pathways inspired by nature to develop new NETs that sequester greenhouse gases into industrially useful chemicals, such as biomass and calcium carbonate. However, synthetic biology continues to encounter difficulties when implementing and scaling up production due to a combination of hard limits (within biology) and ‘soft’ limits (of social and economic costs). Additionally, NETs, along with Ecosystem Technologies in general, operate as climate technofixes, wherein insufficient thought is given to the ethical quandaries arising from releasing designed organisms into the environment, even under controlled conditions. In this paper, we provide a technological and ethical appraisal of synthetic biology approaches to NETs, in the context of climate change mitigation through Ecosystem Technology.